Epidemiological study of burn patients in a tertiary care hospital, Sidhipet district, Telangana - Sreenivas, Talla; Sreenivas, Sudagani; Shridevi, Kotina (International Surgery Journal, 2021)
Background: Burns is a global public health problem, accounting for an estimated 180000 deaths annually and over 1,000,000 cases in India. The exact epidemiological features of burns in each area vary and depends on geography, demography, culture, customs, occupations and several unknown factors. Hence in the present study effort was made to find out epidemiological features and causes associated with burns. Methods: It was a descriptive study, study period been 1 April 2018 to 31 March 2021 (3 years). The study area was a tertiary care hospital in Sidhipet district, Telangana. The sample size was 170 on calculation with the formula. Data was collected from the medical records and reports attached in the file of the patient in the hospital. Ethical issue: Written informed consent or assent and ethical clearance from institutional ethical committee was obtained. Data was analyzed, using microsoft excel version 2019. Results: Majority were from 21-30 years (35.32%), females (66%) and many were flame burns (74%). Major source of flame burns was cooking appliances (62%). Majority of burns have taken place at home (91.9%) and were accidental (86%). Case fatality rate calculated was 8.08%. 96% of wound swabs were positive for bacteria. Conclusions: Mortality due to burns was significantly associated with burns which were suicidal/homicidal in nature, with more burn surface area of >30% and 3rd and 4th degree burns.